Effect of a care plan on the quality of life of the patients with atrial fibrillation - Asghar Khalifehzadeh-Esfahani; Ali Amirzadeh; Jafar Golshahi (Wolters Kluwer Medknow Publications, 2018)
Background: Atrial fibrillation is one of the most common cardiac arrhythmia affecting patients "quality of life (QoL)." With regard to limited number of interventional studies on such patients' QoL, the present study aimed to define the effect of a care plan on the QoL of the patients, hospitalized in coronary care unit (CCU), with atrial fibrillation. Materials and Methods: This is a randomized two-group clinical trial that was conducted on 50 patients, diagnosed with atrial fibrillation and hospitalized in CCU. Fifty patients were selected through convenient sampling and were randomly assigned to study (n = 25) and control (n = 25) groups. Study group underwent an already designed care plan, while the control group received just routine care. QoL was measured by Short Form (SF-36) QoL questionnaire before and one month after intervention. Data were analyzed by t-test through Statistical Package for the Social Sciences. Results: Independent t-test showed a significant difference in mean scores of overall QoL and all of its domains (p < 0.05), except for general health (t = 1.23, p = 0.22) and social function (t = 1.70, p = 0.09). The t-test showed a significant difference in mean (SD) scores of overall QoL in study [51.57 (14.57)] and control [41.80 (18.51)] groups after intervention (t = 2.07, p = 0.04). Conclusions: The results showed that an already designed care plan can result in improvement of QoL in patients with atrial fibrillation. In the present study, a standard care plan was administrated for the patients with atrial fibrillation. Through administration of care plans in clinical settings, nurses' clinical and effective role can be improved.